Comparison of Cost and Perioperative Outcome Profiles for Primary and Revision Posterior Cervical Fusion Procedures. Issue 19 (1st October 2021) - Martini, Michael L.; Baron, Rebecca B.; Gal, Jonathan S.; Neifert, Sean N.; Shuman, William H.; Schupper, Alexander J.; Chapman, Emily K.; McNeill, Ian T.; Steinberger, Jeremy; Caridi, John M.
Abstract : Study Design: Retrospective analysis. Objective: To compare perioperative outcomes and hospitalization costs between patients undergoing primary or revision posterior cervical discectomy and fusion (PCDF). Summary of Background Data: While prior studies found differences in outcomes between primary and revision anterior cervical discectomy and fusion (ACDF), risk, and outcome profiles for posterior cervical revision procedures have not yet been elucidated. Methods: Institutional records were queried for cases involving isolated PCDF procedures to evaluate preoperative characteristics and outcomes for patients undergoing primary versus revision PCDF between 2008 and 2016. The primary outcome was perioperative complications, while perioperative and resource utilization measures such as hospitalization length, required stay in the intensive care unit (ICU), direct hospitalization costs, and 30-day emergency department (ED) admissions were explored as secondary outcomes. Results: One thousand one hundred twenty four patients underwent PCDF, with 218 (19.4%) undergoing a revision procedure. Patients undergoing revision procedures were younger (53.0 vs. 60.5 yrs), but had higher Elixhauser scores compared with the non-revision cohort. Revision cases tended to involve fewer spinal segments (3.6 vs. 4.1 segments) and shorter surgical durations (179.3 vs. 206.3 min), without significant differences in estimated blood loss. There were no significant differences in the overall complication rates ( P  = 0.20), however, the primary cohort had greater rates of required ICU stays ( P  = 0.0005) and non-home discharges ( P  = 0.0003). The revision cohort did experience significantly increased odds of 30-day ED admission ( P  = 0.04) and had higher direct hospitalization ( P  = 0.03) and surgical ( P  < 0.0001) costs. Conclusion: Complication rates, including incidental durotomy, were similar between primary and revision PCDF cohorts. Although prior surgery status did not predict complication risk, comorbidity burden did. Nevertheless, patients undergoing revision procedures had decreased risk of required ICU stay but greater risk of 30-day ED admission and higher direct hospitalization and surgical costs. Level of Evidence: 3 Abstract : This study compared perioperative outcomes and costs between patients undergoing primary (906) or revision (218) posterior cervical discectomy and fusion. Complication rates, including rates of incidental durotomy, were similar between the cohorts. Nevertheless, revision patients had decreased risk of required intensive care unit stay, greater risk of 30-day emergency department admission, and higher hospitalization and surgical costs.